SUMOylation of Argonaute-2 regulates RNA interference activity - Josa-Prado, Fernando (Biochem Biophys Res Commun, 2015)
Post-translational modification of substrate proteins by small ubiquitin-like modifier (SUMO) regulates a vast array of cellular processes. SUMOylation occurs through three sequential enzymatic steps termed E1, E2 and E3. Substrate selection can be determined through interactions between the target protein and the SUMO E2 conjugating enzyme Ubc9 and specificity can be enhanced by substrate interactions with E3 ligase enzymes. We used the putative substrate recognition (PINIT) domain from the SUMO E3 PIAS3 as bait to identify potential SUMO substrates. One protein identified was Argonaute-2 (Ago2), which mediates RNA-induced gene silencing through binding small RNAs and promoting degradation of complimentary target mRNAs. We show that Ago2 can be SUMOylated in mammalian cells by both SUMO1 and SUMO2. SUMOylation occurs primarily at K402, and mutation of the SUMO consensus site surrounding this lysine reduces Ago2-mediated siRNA-induced silencing in a luciferase-based reporter assay. These results identify SUMOylation as a potential regulator of Ago2 activity and open new avenues for research into the mechanisms underlying the regulation of RNA-induced gene silencing.